2001
DOI: 10.1089/108076801753266802
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Efficacy of Travoprost, a Potent and Selective FP Prostaglandin Receptor Agonist

Abstract: Travoprost is the isopropyl ester prodrug of a high affinity, selective FP prostaglandin full receptor agonist. In contrast to travoprost acid's high affinity and efficacy at the FP receptor, there is only sub-micromolar affinity for the DP, EP1, EP3, EP4, IP, and TP receptors. Travoprost produced a lower incidence of ocular irritation than PGF20 isopropyl ester at a dose of 1 microg in the New Zealand albino (NZA) rabbit. Topical ocular application of travoprost produced a marked miotic effect in cats followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
78
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(87 citation statements)
references
References 12 publications
4
78
0
3
Order By: Relevance
“…3,4) They lower IOP by increasing the outflow of aqueous humor via the uveoscleral pathway. 5,6) Some studies have reported the ability of PGF2α to elevate blood pressure. 7,8) Although some clinical trials have reported that topical PGF2α analogs are safe, [9][10][11] they are thought to cause systemic adverse events.…”
mentioning
confidence: 99%
“…3,4) They lower IOP by increasing the outflow of aqueous humor via the uveoscleral pathway. 5,6) Some studies have reported the ability of PGF2α to elevate blood pressure. 7,8) Although some clinical trials have reported that topical PGF2α analogs are safe, [9][10][11] they are thought to cause systemic adverse events.…”
mentioning
confidence: 99%
“…This is a model that we have found to be highly predictive of ocular hypotensive activity in humans (Hellberg et al, 2001;Sharif et al, 2001). Toward this end, we chose to evaluate both selective and nonselective 5-HT 1A agonists and selective 5-HT 2 antagonists.…”
mentioning
confidence: 99%
“…A number of prostaglandin F 2␣ (PGF 2␣ ) analogs are marketed for the treatment of ocular hypertension, a major risk factor for glaucoma. The ocular antihypertensive drugs travoprost (TRAVATAN) and latanoprost (Xalatan) are well characterized prodrugs of FP receptor agonists (Hellberg et al, 2001;Stjernschantz et al, 1995). However, two additional IOPlowering prostaglandin analogs, bimatoprost (Lumigan ) and unoprostone isopropyl ester (Rescula ), have recently been reported to have no observed activity at FP or other known prostaglandin receptors (Bhattacherjee et al, 2001;Woodward et al, 2001) despite being PGF 2␣ analogs.…”
mentioning
confidence: 99%